Postauricular dermoid cyst: A very rare clinicopathological entity (Indian Journal of Case Reports, 2025)
Dermoid cysts (DC) of the postauricular region are extremely rare and often present since childhood. They usually lie dormant for some time and then grow and manifest clinically because of enlargement, rupture, or sometimes extension to surrounding structures. Common differential diagnoses include epidermoid cysts, sebaceous cysts, retroauricular lymph nodes, lipomas, hemangioma, and keloids. We describe a 17-year-old male with an unusual presentation of DC in the subcutaneous tissue of the left retroauricular region. Although extremely rare, DC should be considered in the differential diagnosis of postauricular lumps. Modalities like ultrasonography, computed tomography, and fine needle aspiration cytology help narrow down the diagnosis and rule out any intracranial extension. Complete excision at an early stage is mandatory to avoid recurrence, infection, rupture, and malignant change, and for cosmetic purposes. A histopathological examination is required for confirmation and to rule out any malignant change.